A hypoplastic model for gas hydrate‐bearing sandy sediments. (19th January 2018) - Zhang, Xuhui; Lin, Jia; Lu, Xiaobing; Liu, Lele; Liu, Changling; Li, Mingyao; Su, Yewang
Summary: Gas hydrate‐bearing sediments (GHBSs) have been considered as a potential energy resource. In this paper, the mechanical properties of GHBS are firstly investigated by the integrated test apparatus for synthesis of GHBS using silty sand as skeleton. Triaxial tests indicate an obvious transition of stress‐strain relationship from strain hardening under low hydrate saturation and strain softening under high hydrate saturation. The hypoplastic models coupled with Drucker‐Prager criterion and the Mohr‐Coulomb criterion are proposed to analyze the stress‐strain relationship of GHBS with considering the effective porosity because of the hydrate filling in the pores of GHBS. The strain hardening and softening behaviors are well predicted with less material parameters compared with the classical models. Compared with the test results, the proposed hypoplastic models are verified to be capable of capturing the salient features of the mechanical behaviors of GHBS under the conditions of little temperature change and no hydrate dissociation.